Thumbelina - Andersen; Hans Christian (London Mind to Mind, 2010)
The tale follows the adventures of Thumbelina, a tiny girl no larger than a thumb, who faces various challenges and encounters magical creatures as she seeks her place in the world. Through trials and triumphs, she ultimately finds love and a place where she belongs. This edition captures the enchanting essence of Andersen's original story while making it accessible to today's audience.